Seeing into hearts and minds: Part 2. 'Big data', algorithms, and computational counterinsurgency - Gonzalez, Roberto J (Anthropology today, 2015)
In this second of his two‐part article, the author analyzes the rise of ‘predictive policing’ and its Pentagon connections, reviews two programmes, and poses these in the context of scientists' concerns over artificial intelligence and long‐term human survival.